2020
DOI: 10.1155/2020/7397132
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Correlation of an Autophagy-Related Gene Signature in Patients with Head and Neck Squamous Cell Carcinoma

Abstract: Considerable evidence indicates that autophagy plays a vital role in the biological processes of various cancers. The aim of this study is to evaluate the prognostic value of autophagy-related genes in patients with head and neck squamous cell carcinoma (HNSCC). Transcriptome expression profiles and clinical data acquired from The Cancer Genome Atlas (TCGA) database were analyzed by Cox proportional hazards model and Kaplan–Meier survival analysis to screen autophagy-related prognostic genes that were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
1
20
1
Order By: Relevance
“…The K-M analysis of our model showed a more optimistic trend; the difference in survival curve in the high-and low-risk groups was more significant compared with that of the previous study (He et al, 2021). Moreover, the prognostic risk model of HNSCC patients was more accurate than the models reported in certain previous studies with a preferable AUC for 1 (0.665 vs. 0.634 and 0.663), 3 (0.743 vs. 0.672 and 0.686), and 5 years (0.755 vs. 0.642 and 0.622) (Yang et al, 2020;. Interestingly, the AUC values of our model increased annually, which further strengthened the prognostic effect of the model.…”
Section: Discussioncontrasting
confidence: 55%
“…The K-M analysis of our model showed a more optimistic trend; the difference in survival curve in the high-and low-risk groups was more significant compared with that of the previous study (He et al, 2021). Moreover, the prognostic risk model of HNSCC patients was more accurate than the models reported in certain previous studies with a preferable AUC for 1 (0.665 vs. 0.634 and 0.663), 3 (0.743 vs. 0.672 and 0.686), and 5 years (0.755 vs. 0.642 and 0.622) (Yang et al, 2020;. Interestingly, the AUC values of our model increased annually, which further strengthened the prognostic effect of the model.…”
Section: Discussioncontrasting
confidence: 55%
“…The K-M analysis of our model showed a more optimistic trend; the difference in survival curve in the high- and low-risk groups was more significant compared with that of the previous study ( He et al, 2021 ). Moreover, the prognostic risk model of HNSCC patients was more accurate than the models reported in certain previous studies with a preferable AUC for 1 (0.665 vs. 0.634 and 0.663), 3 (0.743 vs. 0.672 and 0.686), and 5 years (0.755 vs. 0.642 and 0.622) ( Yang et al, 2020 ; Liu B. et al, 2021 ). Interestingly, the AUC values of our model increased annually, which further strengthened the prognostic effect of the model.…”
Section: Discussionmentioning
confidence: 58%
“…Integrin alpha 3 (ITGA3) belongs to the family of integrins, which are heterodimeric integral membrane proteins that function as cell surface adhesion molecules. This gene has been reported in several autophagy-related prognostic models for various tumors, indicating its important role in the progression of tumors 27 – 32 . Mechanistically, it has been reported that miRNA-524-5p inhibits the progression of papillary thyroid carcinoma cells by targeting FOXE1 and ITGA3 in cell autophagy and cycling pathways 33 .…”
Section: Discussionmentioning
confidence: 93%